2008
DOI: 10.1002/fld.1776
|View full text |Cite
|
Sign up to set email alerts
|

A new volume of fluid method in three dimensions—Part I: Multidimensional advection method with face‐matched flux polyhedra

Abstract: SUMMARYA multidimensional advection scheme in 3D based on the use of face-matched flux polyhedra to integrate the volume fraction evolution equation is proposed. The algorithm tends to reduce the formation of 'over/undershoots' by alleviating the over/underlapping of flux polyhedra, thus diminishing the need to use local redistribution algorithms. The accuracy and efficiency of the proposed advection algorithm, which are analyzed using different tests with prescribed velocity field, compare well with other mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 27 publications
9
98
0
Order By: Relevance
“…Then, the ability of the proposed method to handle interfaces that undergo large deformation is analyzed in two different flows with non-uniform vorticity. All the results are obtained using the multidimensional advection algorithm FMFPA-3D proposed by us in a companion paper [20]. The results are compared with those obtained with different reconstruction methods implemented in this work and with recent results available in the literature.…”
Section: Resultsmentioning
confidence: 91%
“…Then, the ability of the proposed method to handle interfaces that undergo large deformation is analyzed in two different flows with non-uniform vorticity. All the results are obtained using the multidimensional advection algorithm FMFPA-3D proposed by us in a companion paper [20]. The results are compared with those obtained with different reconstruction methods implemented in this work and with recent results available in the literature.…”
Section: Resultsmentioning
confidence: 91%
“…It only works with Cartesian grids. The algorithm implemented is a merge of Malik et al [6] and Hernandez et al [5] schemes. It follows a brief summary of the algorithm: 1.…”
Section: Evaluation Of Surface Tension Effects: Hf and Youngs Comparisonmentioning
confidence: 99%
“…VOF method is used to follow interface. Two different methods to reconstruct interface are compared: Youngs method [4] and Height Function (HF) method [5][6][7]. The comparison is carried out analyzing algorithms performances through standard test cases.…”
Section: Introductionmentioning
confidence: 99%
“…Horgue et al [29] suggested that the spurious current could be reduced by using the High-Resolution Interface Capturing (HRIC) scheme employed in FLUENT [30], although the interface is more diffusive and the liquid film becomes thicker with this approach compared with the Geo-Reconstruct scheme [31]. Magnini et al [23,24] coupled the VOF-CSF method with the Height Function method [32,33] for predicting the local surface shape to reduce spurious currents. A critical Capillary number exists below which these unphysical flows affect the simulation results.…”
Section: Introductionmentioning
confidence: 99%